Agricultural wages in India: trends and determinants - Sant Kumar; Md Ejaz Anwer; T K Immanuelraj; Sumant Kumar; H P Singh; Sarba N Mishra; S K Sarkar (Agricultural Economics Research Review, 2023)
Structural change in employment has been slow, particularly in agriculture, and its share in income has declined faster than employment has transitioned. This shift requires us to focus on the trends in agricultural wages. Our analysis shows that non-farm wages, the MGNREGS, irrigation facility, and rural literacy have a significant and positive effect on agricultural wages, and farm mechanization helps reduce the wage rate significantly. Creating more non-farm employment opportunities and supporting literacy programmes and irrigation will help improve farm wages, and incentivizing farm mechanization will reduce the cost of cultivation for farmers and the rural poor.